Vandetanib inhibits growth of adenoid cystic carcinoma in an orthotopic nude mouse model. - Choi, S; Sano, D; Cheung, M; Zhao, M; Jasser, SA; Ryan, A; Mao, L; Chen, W; El-Naggar, A; Myers, J (2008)
PURPOSE: Adenoid cystic carcinoma (ACC) can often be controlled with surgery and postoperative adjuvant radiotherapy but is also characterized by late local recurrence and distant metastasis. No effective systemic therapeutic agents have been found to alter the natural history of ACC. Therefore, new therapeutic approaches are needed. In this study, we evaluated whether vandetanib (Zactima), a potent inhibitor of vascular endothelial growth factor receptor-2 (VEGFR-2) and epidermal growth factor receptor (EGFR) tyrosine kinases, had antitumor efficacy in vitro and in an orthotopic nude mouse model of human ACC. EXPERIMENTAL DESIGN: The in vitro effects of vandetanib were assessed in three ACC cell lines on cell growth, apoptosis, and VEGFR-2 and EGFR phosphorylation levels. The in vivo antitumor activity of vandetanib was examined in nude mice bearing parotid gland ACC tumors. The mice were treated for 4 weeks with vandetanib (50 mg/kg/d) or placebo (control). Tumors were resected at necropsy, and immunohistochemical and immunofluorescence staining were done. RESULTS: In vitro, vandetanib caused dose-dependent inhibition of VEGFR-2 and EGFR phosphorylation in ACC cells. Vandetanib also inhibited the cell proliferation and induced their dose-dependent apoptosis. In vivo, mice in the vandetanib group had tumor volumes significantly lower than those in the control group (P < 0.01). In addition, immunohistochemical staining showed a decrease in microvessel density and an increase in apoptosis of both tumor cells and endothelial cells within the tumor xenografts. CONCLUSION: These results suggest that vandetanib inhibits the growth of ACC in vitro and in vivo, making it a promising novel agent for the treatment of ACC.